Process parameters tuning and online re-slicing for robotized additive manufacturing of big plastic objects. (February 2019) - Rebaioli, Lara; Magnoni, Paolo; Fassi, Irene; Pedrocchi, Nicola; Molinari Tosatti, Lorenzo
Highlights: AM system for big plastic objects (anthropomorphic robot + industrial extruder). Tuning procedure to set a suitable range of process parameters. Closed loop control strategy able to correct the robot height. Online re-slicing algorithm to preserve the original size of the manufactured object. Abstract: Complex parts can be successfully manufactured by means of Additive Manufacturing (AM) techniques based on thermoplastic polymer extrusion, whose use for mass production is restricted by their slow printing speed. To address this limitation, a flexible AM platform for big plastic objects has been realized mounting an industrial screw-based extruder on an anthropomorphic robot. An experimental campaign has been performed to set a suitable range of relevant process parameters, with the aim of ensuring a regular deposited layer geometry. Moreover, a closed-loop control strategy has been developed to correct the robot height based on data measured during the material deposition, thus further improving the process parameter setting and compensating the material shrinkage or other unexpected defects. Eventually, an online re-slicing algorithm has been implemented to preserve the desired height of the manufactured object, despite the layer height changes. The proposed approach allows a deposition flow rate up to 1250 cm 3 /h within a building volume limited only by the robot workspace.